A reflexão de professores de inglês em interações via e-mail - Marcicano, Juliana Godinho Ragusa (2010)
This dissertation lies within the area of the English teacher s reflective development and aims at describing and interpreting the phenomenon English teachers reflection in interactions through e-mail, through the identification of the questions that intrigue these participating teachers. To reach this goal, this investigation describes and interprets the phenomenon above from the point of view of the experience lived by myself, the researcher, as well as by seven participating teachers. The theoretical underpinning for this study is the concept of reflective development, based on the contributions of Dewey (1916, 1910/1933, 1938/1997, 1986/2008) Schön (1983, 1987, 1992a, 1992b), Freire (1970/1983, 1992, 2002, 2004), Vygotsky (1984/1998, 1989/2008), Kemmis (1987), Zeichner (1993, 2003) among others. From a qualitative standpoint, the methodological approach is the hermeneutic-phenomenological one, which aims at associations of retrospective descriptions and (re-)interpretations of lived experience (Ricoeur, 1986, 2002; van Manen, 1990; Freire, 1998, 2006, 2007a, 2007b). The texts which provided the interpretation basis were collected along two different semesters, when through 76 e-mail messages and 5 presential meetings it was possible to: (1) draw the profile of the English teachers who work for public schools and participate in this research, (2) identify the subjects which lead them to reflections upon their practices, and (3) document the reflective process unleashed. The interpretation of the collected texts was made according to the textualization and thematization processes proposed by van Manen (1990), and systematized by the refining and ressignification procedures suggested by Freire (2006, 2007a, 2007b) which show the themes that structure the investigated phenomenon. The interpretation of the texts reveal that English teachers reflection in interactions through e-mail is lived differently by the two groups formed by the participating teachers: in the first one, Caderno, difficulty, time, and identification are the emerging themes; in the second one, identification, practice and lack of time are the themes that display the nature of the experience lived by part of the participants in this research